2019
DOI: 10.3390/biology8020022
|View full text |Cite
|
Sign up to set email alerts
|

Factors that May Protect the Native Hibernator Syrian Hamster Renal Tubular Epithelial Cells from Ferroptosis Due to Warm Anoxia-Reoxygenation

Abstract: Warm anoxia-reoxygenation induces ferroptotic cell death in mouse proximal renal tubular epithelial cells (RPTECs), whereas RPTECs of the native hibernator Syrian hamster resist cell death. Clarifying how hamster cells escape ferroptosis may reveal new molecular targets for preventing or ameliorating ischemia-reperfusion-induced human diseases or expanding the survival of organ transplants. Mouse or hamster RPTECs were subjected to anoxia and subsequent reoxygenation. Cell death was assessed with the lactated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
3
12
0
Order By: Relevance
“…Notably, confirming the pathophysiological difference between the two phases of I-R injury, previous studies showed that during ischemia, RPTECs death ensues through apoptosis (11,12). In contrast to this, reperfusion induces lipid peroxidation and ferroptotic cell death (12)(13)(14).…”
Section: Introductionsupporting
confidence: 52%
“…Notably, confirming the pathophysiological difference between the two phases of I-R injury, previous studies showed that during ischemia, RPTECs death ensues through apoptosis (11,12). In contrast to this, reperfusion induces lipid peroxidation and ferroptotic cell death (12)(13)(14).…”
Section: Introductionsupporting
confidence: 52%
“…With regards reoxygenation-induced cell death, previous studies using primary RPTECs and similar experimental conditions have demonstrated that reoxygenation leads to lipid peroxidation and ferroptotic cell death (5,6). Elegant research using isolated murine renal tubules detected the same (7).…”
Section: Discussionmentioning
confidence: 74%
“…During ischemia, cell energy collapse induces cell death, whereas during reperfusion, cell death results from increased reactive oxygen species (ROS) production ( 1 3 ). Regarding renal tubular epithelial cells, a study demonstrated that under anoxia, cells die through apoptosis, whereas reoxygenation induces lipid peroxidation-induced cell death, also known as ferroptosis ( 5 , 6 ). The latter has also been detected in isolated mouse renal tubules, confirming the different pathophysiology of ischemia- and reperfusion-induced cell injury ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ferroptosis or membrane lipid peroxidation-induced cell death plays an essential role in I-R ROS-mediated cell death [21]. In non-hibernating species, ferroptosis has been identified as a type of renal tubular epithelial cell death due to I-R and the cause of subsequent AKI [25][26][27][28][29]. Various other types of cell death have also been incriminated for I-R-induced AKI [30].…”
Section: Discussionmentioning
confidence: 99%